2022
DOI: 10.1097/ee9.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Short-term ambient air pollution exposure and risk of atrial fibrillation in patients with intracardiac devices

Abstract: Introduction: Atrial fibrillation (AF) is the most common cardiac arrhythmia and is associated with substantial morbidity and mortality. Short-term exposure to fine particulate matter (PM 2.5 ) has been causally linked to higher risk of cardiovascular disease, but the association with atrial fibrillation (AF) is less clear. Methods: We conducted a time-stratified case-crossover study to estimate the association between short-term air pollution levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Previous findings on the association of air pollutants with arrhythmia have been mixed. 24 , 26 , 47 , 48 Most studies were subject to the ecological fallacy (the bias that may occur when associations that exist between variables at the aggregate level may not represent the true associations that exist at the individual level), 49 , 50 and were limited in sample size, geographical coverage and time specification. 21 , 23 , 24 , 26 Our case–crossover study strengthens previous findings by providing large-scale, individual-level evidence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous findings on the association of air pollutants with arrhythmia have been mixed. 24 , 26 , 47 , 48 Most studies were subject to the ecological fallacy (the bias that may occur when associations that exist between variables at the aggregate level may not represent the true associations that exist at the individual level), 49 , 50 and were limited in sample size, geographical coverage and time specification. 21 , 23 , 24 , 26 Our case–crossover study strengthens previous findings by providing large-scale, individual-level evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistency of these findings may be explained by the difference in air pollution mixture, climate conditions and population susceptibility, as well as the study design, statistical power and exposure lags that were used in the various studies. 21 , 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a time-stratified case-crossover study observed an increased risk of AF episodes with PM 2.5 levels. 37 A Chinese study found a 3.1% increased odds ratio of AF for every 10 µg/m³ increase in long-term PM 2.5 exposure. 38 Additionally, a Taiwanese report revealed a positive association between elevated PM 2.5 levels and the emergence of new AF cases.…”
Section: Ambient Environmentmentioning
confidence: 99%